2018
DOI: 10.3389/fimmu.2018.00585
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T-Cells: Potential Regulator of Tissue Repair and Regeneration

Abstract: The identification of stem cells and growth factors as well as the development of biomaterials hold great promise for regenerative medicine applications. However, the therapeutic efficacy of regenerative therapies can be greatly influenced by the host immune system, which plays a pivotal role during tissue repair and regeneration. Therefore, understanding how the immune system modulates tissue healing is critical to design efficient regenerative strategies. While the innate immune system is well known to be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
216
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(234 citation statements)
references
References 113 publications
(150 reference statements)
5
216
0
13
Order By: Relevance
“…Much still remains to be determined about how different macrophage populations interact with other cell types in tendon to modulate tissue repair. The adaptive immune system is known to play an important role in tissue pathology in disease states, but its role in healing of various musculoskeletal injuries is an emerging area of study (17), and even less is known about lymphocytes in tendon healing. There is also cross-talk between the innate and adaptive immune systems during tissue repair (12).…”
Section: Discussionmentioning
confidence: 99%
“…Much still remains to be determined about how different macrophage populations interact with other cell types in tendon to modulate tissue repair. The adaptive immune system is known to play an important role in tissue pathology in disease states, but its role in healing of various musculoskeletal injuries is an emerging area of study (17), and even less is known about lymphocytes in tendon healing. There is also cross-talk between the innate and adaptive immune systems during tissue repair (12).…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + T cells are divided into two categories of CD4 + CD25 À effector T cells and CD4 + CD25 + Foxp3 + regulatory T cells (Tregs). Tregs are regarded as anti-inflammatory cells that play a vital role in maintaining immune homeostasis (Lee & Lee 2018) and can facilitate regeneration of various tissues by creating a beneficial immune microenvironment via immune cells modulation or by directly activating progenitor cells (Li et al 2018). Tregs are a specialized subpopulation of T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Tregs are produced in the thymus or converted from naive T cells in the peripheral environment, which is called Treg conversion (Chen et al 2003). Tregs are regarded as anti-inflammatory cells that play a vital role in maintaining immune homeostasis (Lee & Lee 2018) and can facilitate regeneration of various tissues by creating a beneficial immune microenvironment via immune cells modulation or by directly activating progenitor cells (Li et al 2018). Recently, several studies have reported that MSCs upregulated Tregs, which served to regulate the local or systemic inflammation response to promote tissue regeneration (Wu et al 2014, Liu et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…One of the underlying mechanisms associated with T reg ‐mediated wound healing is assumed to be the suppression of pro‐inflammatory stimuli. Such T reg ‐mediated immune suppression appears to be a critical factor allowing for the progression of the wound‐healing process . T regs utilize a number of different mechanisms to locally mediate their immune‐suppressive function .…”
Section: Immune‐mediated Roles Of Regulatory T‐cells During Wound Heamentioning
confidence: 99%
“…Such T reg -mediated immune suppression appears to be a critical factor allowing for the progression of the wound-healing process. 13 T regs utilize a number of different mechanisms to locally mediate their immune-suppressive function. 14 These mechanisms include the local activation of bio-active transforming growth factor (TGF)b, 15,16 the secretion of the immune-suppressive cytokine IL-10 17 or the conversion of local adenosine monophosphate into adenosine.…”
Section: Immune-mediated Roles Of Regulatory T-cells During Wound Heamentioning
confidence: 99%